The Plant Decapeptide OSIP108 Can Alleviate Mitochondrial Dysfunction Induced by Cisplatin in Human Cells - Pieter Spincemaille; Hamed Alborzinia; Jeroen Dekervel; Petra Windmolders; Jos van Pelt; David Cassiman; Olivier Cheneval; David J. Craik; Julia Schur; Ingo Ott; Stefan Wölfl; Bruno P. A. Cammue; et al. (Molecules, 2014)
We investigated the effect of the Arabidopsis thaliana-derived decapeptide OSIP108 on human cell tolerance to the chemotherapeutic agent cisplatin (Cp), which induces apoptosis and mitochondrial dysfunction. We found that OSIP108 increases the tolerance of HepG2 cells to Cp and prevents Cp-induced changes in basic cellular metabolism. More specifically, we demonstrate that OSIP108 reduces Cp-induced inhibition of respiration, decreases glycolysis and prevents Cp-uptake in HepG2 cells. Apart from its protective action against Cp in human cells, OSIP108 also increases the yeast Saccharomyces cerevisiae tolerance to Cp. A limited yeast-based study of OSIP108 analogs showed that cyclization does not severely affect its activity, which was further confirmed in HepG2 cells. Furthermore, the similarity in the activity of the D-stereoisomer (mirror image) form of OSIP108 with the L-stereoisomer suggests that its mode of action does not involve binding to a stereospecific receptor. In addition, as OSIP108 decreases Cp uptake in HepG2 cells and the anti-Cp activity of OSIP108 analogs without free cysteine is reduced, OSIP108 seems to protect against Cp-induced toxicity only partly via complexation. Taken together, our data indicate that OSIP108 and its cyclic derivatives can protect against Cp-induced toxicity and, thus, show potential as treatment options for mitochondrial dysfunction- and apoptosis-related conditions.